STUDENTS’ PERCEPTION TOWARD ELECTRONIC EXTENSIVE READING MATERIALS BASED ON BANJAR STORIES - Umar, Vebrianti; Perdana, Indra; Ristati, Ristati (Program Studi Magister Pendidikan Bahasa Inggris, Program Pascasarjana, Universitas Palangka Raya, 2021)
At university education level, Extensive reading is an course that taught at third or fourth semester. The material for this course should be easy and interested, because the students should enjoy everything they read. However, in this crucial situation of pandemic covid 19, the process of teaching and learning extensive reading is conducted in online mode to avoid the spreading of corona virus. Thus, the lecturer need an materials that support the online learning. Developing an Electronic instructional material is an solution to solve the lecturer’s problem in teaching and learning of extensive reading. One of step in the developing the materials is implementation, in which the students will give their response about the e-instructional material.Conducting this research is for explaining the students’ perception towards Electronic Extensive Reading Materials Based Stories of Banjar. This research done at fourth semester students of Lambung Mangkurat University. Quantitative with design survey applied as the method of this research. The questionnaire is instrument used to obtain the data.The result revealed that most of students respond positive towards this Electronic Extensive Reading Materials Based on Banjar Stories . They agree that it is interesting and flexible to use. It means this E-instructional material is feasible to use as an reference for supporting extensive reading course.